1989
DOI: 10.1111/j.1365-2125.1989.tb03492.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of cilazapril in patients with renal failure.

Abstract: 1. The pharmacokinetics of a single 1 mg dose of cilazapril were determined in six subjects with normal renal function and in 19 uraemic patients with various degrees of renal impairment. 2. Significant decreases in systolic and diastolic blood pressure were noted in all groups of subjects between 2 and 8 h after administration of 1 mg cilazapril. 3. There was a significant correlation between ACE inhibition at 24 h and creatinine clearance (CrCL). 4. For cilazapril, Cmax and tmax were independent of creatinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
1

Year Published

1989
1989
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 6 publications
2
13
1
Order By: Relevance
“…Longer times to peak after lower dosages of cilazapril have also been reported in normal volun teers [2], In addition, the slower excretion of cilazaprilat in the low clearance groups may have contributed to the longer times to peak. Theoretically, slower intestinal In our patients with normal as well as in those with absorption of cilazapril in the low clearance groups may impaired renal function the pharmacokinetic data of the also explain this difference, but studies with other ACE Discussion single dose part were comparable with the results inhibitors are not in favour of such obtained by others [1,3,4]. A strong relationship…”
Section: Ab-s Ab-i Cd-s Cd-isupporting
confidence: 67%
See 2 more Smart Citations
“…Longer times to peak after lower dosages of cilazapril have also been reported in normal volun teers [2], In addition, the slower excretion of cilazaprilat in the low clearance groups may have contributed to the longer times to peak. Theoretically, slower intestinal In our patients with normal as well as in those with absorption of cilazapril in the low clearance groups may impaired renal function the pharmacokinetic data of the also explain this difference, but studies with other ACE Discussion single dose part were comparable with the results inhibitors are not in favour of such obtained by others [1,3,4]. A strong relationship…”
Section: Ab-s Ab-i Cd-s Cd-isupporting
confidence: 67%
“…the study of ind clearance of cilazaprilat on the other hand was [3 ] observed. Time to peak was longer in patients with patients with a low creatinine clearance.…”
Section: Ab-s Ab-i Cd-s Cd-imentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, slower intestinal absorption of cilazapril in the low clearance groups may also explain this difference, but studies with other ACE inhibitors are not in favour of such a mechanism [lo]. We can not compare our results with the study of Fillastre et al who found a higher C,,, in patients with renal insufficiency [3], since we used a lower dose in patients with a low creatinine clearance. Concentrations of cilazaprilat at 96 h were low and the decline of the logarithm of the cilazaprilat concentration was not linear and showed a wide interindividual variation as reported by others [2,81.…”
Section: Discussioncontrasting
confidence: 56%
“…The results of studies on the long-term administration of cilazapril sug gest that the dosage should be reduced in this case [7,8], In summary, of note is that most physi cians who prescribe ACE-Is use these drugs in hyperdipsia-associated disease states, such as congestive heart failure, hypertension, renal failure, without knowing its specific effect on thirst. An antidipsogenic effect of ACE-I through CNS action is of particular interest in this regard.…”
Section: Discussionmentioning
confidence: 99%